OP0126 A phase 2 study of safety and efficacy of anabasum (JBT-101) in systemic sclerosis. (15th June 2017) - Spiera, R; Hummers, L; Chung, L; Frech, T; Domsic, R; Furst, D; Gordon, J; Mayes, M; Simms, R; Constantine, S; White, B
Abstract : Background: Anabasum (JBT-101) is a synthetic, oral, non-immunosuppressive, preferential CB2 agonist. It inhibits onset and activates resolution of innate immune responses in animal models of systemic sclerosis (SSc). Objectives: Evaluate safety and efficacy of anabasum in SSc Methods: A double-blind, randomized, placebo (PBO)-controlled Phase 2 trial dosed 42 diffuse cutaneous SSc subjects with disease duration ≤6 years on stable medication including immunosuppressive drugs. Subjects received anabasum 5 mg QD, 20 mg QD, or 20 mg BID on Days 1–28, then 20 mg BID on Days 29–84, or PBO on Days 1–84. Subjects were followed off study drug on Days 85–113. The primary safety outcome was treatment-emergent adverse events (TEAEs). The primary efficacy outcome was improvement in ACR Combined Response Index in diffuse cutaneous Systemic Sclerosis (CRISS) score, combined anabasum group vs PBO, Days 29–113 (end of Weeks 4–16). The five domains of the ACR CRISS are the modified Rodnan skin score, HAQ-DI, patient and physician global assessments, and FVC % predicted. Results: Of 42 dosed subjects, 27 (64%) received anabasum and 15 (36%) received PBO. Three anabasum subjects withdrew: 1 (3.7%) for a TEAE of moderate dizziness; 1 withdrew consent; and 1 by physician decision. One PBO subject withdrew consent. Baseline demographic and CRISS domain scores were similar except slightly more anabasum subjects used background immunosuppressive drugs (93% versus 80%, anabasum vs PBO). Seventeen (63%) anabasum subjects had 66 TEAEs, and 9 (60%) PBO subjects had 35 TEAEs. There were no serious, severe, or unexpected TEAEs related to anabasum. Severity and relationship of TEAEs to study drug were similar in both groups. The most frequent TEAEs by MedDRA system (% anabasum vs % PBO) were: nervous system (37% vs 27%); general disorders (30% vs 7%); gastrointestinal (22% vs 20%); infections (22% vs 20%); musculoskeletal (22% vs 13%); and investigations (0% vs 20%). The most frequent TEAEs in anabasum subjects were dizziness (22%) and fatigue (19%) which were usually mild. Anabasum subjects had greater improvement in ACR CRISS scores than PBO subjects (mixed model repeated measures analysis, p=0.044, 1-sided). The median ACR CRISS scores at the end of Weeks 4, 8, 12, and 16 (anabasum vs PBO) were 3.0% vs 1.0%, 19.0% vs 1.0%, 27.5% vs 1.0%, and 33.0% vs 1.0%, respectively. Among anabasum subjects, ∼50% had ACR CRISS ≥20% after 8 weeks of dosing. The individual domains of the ACR CRISS score showed greater improvement, improvement that reached minimal important differences in several domains, and less worsening in anabasum vs PBO groups. Anabasum subjects had greater improvement in SSc skin symptoms and itch. Plasma metabolipidomic profiles showed anabasum, not PBO, shifted lipid mediator production to increase pro-resolving vs pro-inflammatory lipid mediators. Conclusions: Anabasum provided significant and medically meaningful efficacy in SSc as assessed by the ACR CRISS score and its individual domains and had acceptable safety and tolerability in this Phase 2 trial. These data support continued clinical development of anabasum for the treatment of SSc. Disclosure of Interest: R. Spiera: None declared, L. Hummers: None declared, L. Chung: None declared, T. Frech: None declared, R. Domsic: None declared, D. Furst: None declared, J. Gordon: None declared, M. Mayes: None declared, R. Simms: None declared, S. Constantine Employee of: Corbus Pharmaceuticals, Inc., B. White Employee of: Corbus Pharmaceuticals, Inc.